Smak zielonych pomarańczy. O książce Małgorzaty Chrobak Bohater literatury dziecięcej i młodzieżowej z okresu PRL-u. Między kreacją a recepcją, Kraków 2019 - Kania, Agnieszka (Paidia i Literatura, 2021)
The article discusses the content of the book by Małgorzata Chrobak, The Hero of Polish Children’s and Young Adult Literature from the PRL Period. Between Creation and Reception, valuable for a diverse audience, including young researchers of literature. The author of the review emphasizes the cognitive value of the first chapter of the monograph, which contains a description of the customs of the PRL period, thanks to the analysis of contemporary works for a young audience set in socialist Poland. Next, the content of the second chapter of the book, which deals with the definition of young adult literature from various perspectives, is presented. The third chapter, entitled “The Hero of Young Adult Literature in the Face of Initiation”, written in the spirit of cultural poetics, is a successful analysis of the creation of several heroes from novels from the PRL period. In the last, fourth chapter of the book, Agnieszka Kania notices a certain lack of examples in an interestingly thought-out and presented clash of the heroes with various aspects of the reality of the People’s Republic of Poland.